FATTY ACID AND TOCOCHROMANOL PATTERNS OF SOME ISATIS L. (BRASSICACEAE) SPECIES FROM TURKEY - Bagci, Eyup; Ozcelik, Hasan (Pakistan Botanical Soc, 2009)
During investigations of new sources of higher plant lipids, seed fatty acid compositions and the tocopherol contents of some Isatis sp. (Isatis cappadocica subsp. steveniana, I. kotschyana, I. candolleana, I. spectabilis, I. glauca subsp. glauca and I. kozlowskyi) (Brassicaceae) were investigated by using GC and HPLC system. Some of the species are endemic to Turkey. All the Isatis species showed the same pattern of fatty acids. Linolenic and erucic acids were found as the abundant compounds. Tocochromanol derivatives of the seed oil showed more differences between Isatis species. Alpha, beta, gamma and delta tocopherols were the main compounds. Total tocopherol contents of Isatis species studied were found higher than the total tocotrienols. Polyunsaturated fatty acid concentration of Isatis genus patterns were found higher than most of the family and genera patterns in higher plant groups.
Keywords: Seed Oils; Tocopherols; Lesquerella